Profitability Analysis of E-Sports Industry: A Case Study of Suzhou XingLi Network Technology Co., LTD - Gao, Hongyun; Li, Dan; Chen, Shuang (Transactions on Economics, Business and Management Research, 2024)
As a new industry in the Internet era, e-sports industry stood among many industries despite the outbreak of COVID-19 at the end of 2019, becoming one of the few industries not affected by the epidemic.Suzhou XingLi Network Technology Co. Ltd. is a prominent example in the e-sports industry. Profitablity analysis of XingLi is used to unerstand the operating model and provide reasonable advices. Factor analysis and trend analysis are used, through the analysis of the change trend combined with the industry related situation and market policy, the promotion strategy suitable for electronic sports club is given.